2002
DOI: 10.2214/ajr.178.5.1781053
|View full text |Cite
|
Sign up to set email alerts
|

CT Screening for Lung Cancer

Abstract: In CT screening for lung cancer, the detected nodule commonly is either only part-solid or nonsolid, but such a nodule is more likely to be malignant than a solid one, even when nodule size is taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
198
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 823 publications
(211 citation statements)
references
References 13 publications
8
198
0
5
Order By: Relevance
“…This markedly reduces follow-up requirements. To fully document all interim diagnoses occurring between the annual rounds of screening, the protocol requires that each person who has not returned for repeat screening be followed up to 18 months after their prior screening [9,18]. If no cancer has been identified by either a symptom-prompted workup or any other reason, then the person is considered to have stopped participation in the screening program and no further follow-up is required.…”
mentioning
confidence: 99%
“…This markedly reduces follow-up requirements. To fully document all interim diagnoses occurring between the annual rounds of screening, the protocol requires that each person who has not returned for repeat screening be followed up to 18 months after their prior screening [9,18]. If no cancer has been identified by either a symptom-prompted workup or any other reason, then the person is considered to have stopped participation in the screening program and no further follow-up is required.…”
mentioning
confidence: 99%
“…Furthermore, we only assessed pure GGOs in this study and did not consider part‐solid GGOs, which have a higher incidence of malignancy than either pure GGOs or solid nodules (16) . Although we did not examine part‐solid GGOs, pure GGOs tend to have an intrinsically lower attenuation and, therefore, lower conspicuity, making them more difficult to detect than GGOs with a solid component; thus, we assume that our analysis of pure GGOs would also apply to part‐solid GGOs.…”
Section: Discussionmentioning
confidence: 99%
“…The malignancy rate of nodular ground glass opacity with solid component within it was also found to be 93% [29]. Henschke et al (2002) found malignancy rates among findings of nodular ground-glass opacity for lesions with and without a solid component as 63% and 18% respectively [19]. Persistent finding of nodular ground glass opacity in CT is highly suggestive of neplastic condition.…”
Section: Appearance Of Ground Glass Opacity (Ggo) Nodules In Ctmentioning
confidence: 92%
“…The ground-glass component represents lepidic growth or mucin production. Aoki et al (2000) showed that increasing solid components within a ground-glass nodule correlated with more aggressive behavior [18] a screening study by Henschke et al showed a higher rate of malignancy among mixed SPNs (63%) compared with nonsolid (18%) and solid SPNs (7%) [19].…”
Section: Attenuationmentioning
confidence: 99%